2021
DOI: 10.3390/app11135993
|View full text |Cite
|
Sign up to set email alerts
|

Independent Double-Boost Interleaved Converter with Three-Level Output

Abstract: This paper introduces a novel converter topology based on an independent controlled double-boost configuration. The structure was achieved by combining two independent classic boost converters connected in parallel at the input and in series at the output. Through proper control of the two boost converters, an interleaved topology was obtained, which presents a low ripple for the input current. Being connected in series at the output, a three-level structure was attained with twice the voltage gain of classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In papers [13,14], the operation of the IDBIC converter is described and analyzed. Here, it is shown that the converter's switching states and operation modes are influenced by the value of the duty cycle.…”
Section: General Representation Of the Switching States In Ccmmentioning
confidence: 99%
See 3 more Smart Citations
“…In papers [13,14], the operation of the IDBIC converter is described and analyzed. Here, it is shown that the converter's switching states and operation modes are influenced by the value of the duty cycle.…”
Section: General Representation Of the Switching States In Ccmmentioning
confidence: 99%
“…Therefore, for CCM operation, the possible switching states of the converter are depicted in Figure 1. Moreover, in addition to the mentioned papers, the representations in Figure 1 For a duty cycle less than 50%, the switching states of the converter will be S1-S2-S5 S3, and in the case of the duty cycle exceeding 50%, the switching states will take the form of S4-S5-S4-S1 [13].…”
Section: General Representation Of the Switching States In Ccmmentioning
confidence: 99%
See 2 more Smart Citations
“…The topology studied in this paper and shown in Figure 1 effectively reduces the volume and cost of having a (big) single-output capacitor (see, for example, [9][10][11]); this is achieved by lowering the voltage rating because of a symmetric connection of two capacitors. Although other double-series unidirectional capacitor topologies were presented in [12], the configuration used in this paper requires only two switches, can be expanded for bidirectional usage (adding two more switches), and provides significant voltage gain from moderate duty cycles, thus reducing conduction losses. Related topologies and their characteristics were also presented in a review [13] and in the literary works of [14][15][16][17]; however, none of the above include the dynamic analysis of the topology used in this paper, and, nowadays, knowing power converters' properties-such as their controllability and stability in closed-and open-loop conditions-is indispensable.…”
Section: Introductionmentioning
confidence: 99%